Long-term trends in the ionosphere and upper atmosphere parameters - Bremer, J.; Alfonsi, Lu.; Bencze, P.; Lastovicka, J.; Mikhailov, A. V.; Rogers, N. (Annals of Geophysics, 2004)
The first part of the paper is directed to the investigation of the practical importance of possible longterm trends in the F2-layer for ionospheric prediction models. Using observations of about 50 different ionosonde stations with more than 30 years data series of foF2 and hmF2, trends have been derived with the solar sunspot number R12 as index of the solar activity. The final result of this trend analysis is that the differences between the trends derived from the data of the individual stations are relatively large, the calculated global mean values of the foF2 and hmF2 trends, however, are relatively small. Therefore, these small global trends can be neglected for practical purposes and must not be considered in ionospheric prediction models. This conclusion is in agreement with the results of other investigations analyzing data of globally distributed stations. As shown with the data of the ionosonde station Tromsø, however, at individual stations the ionospheric trends may be markedly stronger and lead to essential effects in ionospheric radio propagation. The second part of the paper deals with the reasons for possible trends in the Earth’s atmo- and ionosphere as investigated by different methods using characteristic parameters of the ionospheric D-, E-, and F-regions. Mainly in the F2-region different analyses have been carried out. The derived trends are mainly discussed in connection with an increasing greenhouse effect or by long-term changes in geomagnetic activity. In the F1-layer the derived mean global trend in foF1 is in good agreement with model predictions of an increasing greenhouse effect. In the E-region the derived trends in foE and h´E are compared with model results of an atmospheric greenhouse effect, or explained by geomagnetic effects or other anthropogenic disturbances. The trend results in the D-region derived from ionospheric reflection height and absorption measurements in the LF, MF and HF ranges can at least partly be explained by an increasing atmospheric greenhouse effect.